Influence of Interstitial Variables on Employees’ Loyalty Linked to Knowledge Management and Transformational Leadership Affecting the Crisis Management Strategies of the Accommodation Business groups in Thailand - Tankaeo, Adunyadet; Phorncharoen, Irada; Harasarn, Anothai (Journal of Management Science Chiangrai Rajabhat University, 2023)
The objectives of this research were (1) to study the influence of the interstitial variables of the employees’ loyalty linked to knowledge management and transformational leadership affecting the crisis management strategies of the accommodation business groups in Thailand, and (2) to examine the consistency of the causal relationship patterns of the interstitial variables and the factors influencing the crisis management strategies. The samples used in the research were 580 accommodation administrators randomized by multi-stage sampling. The research instrument was a questionnaire. The statistics were the structural equation modelling. The research findings were as follows. (1) Knowledge management has a direct influence on crisis management strategies. has a path coefficient size of .228 with statistical significance at the level of .001, the indirect influent path of the knowledge management affecting the crisis management strategies through the employees’ loyalty had the path coefficient at .205 with the statistical significance at the level of .001. The total of the influence of the knowledge management influencing the crisis management strategies through the employees’ loyalty had the path coefficient at .433 with the statistical significance at the level of .001. Transformational leadership directly influences crisis management strategies. had a path coefficient size of .206 with statistical significance at the level of .001, the indirect path of the transformational leadership affecting the crisis management strategies of the accommodation business groups through the employees’ loyalty had the path coefficient at .229 with the statistical significance at the level of .001. The total of the influence of the transformational leadership influencing the crisis management strategies through the employees’ strategies had the path coefficient at .434 with the statistical significance at the level of .001. (2) According to the examination of the consistency of the causal relationship patterns of the interstitial variables and the factors influencing the crisis management strategies, the findings showed that the model fit the empirical data at c2/df =1.073, p-value=.083, GFI=.939, AGFI=.932, CFI=.970, RMSEA=.011, RMR=.033